One-Piece Modified Gasket Seal Technique - Wessell, Aaron; Singh, Ameet; Litvack, Zachary (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objectives Review the effectiveness of a modified gasket seal technique utilizing a porous high-density polyethylene plate/rectus sheath fascia construct without fat grafting for primary closure of anterior defects following endoscopic skull base surgery.Design Retrospective review (2011–2012).Setting Single academic medical center.Methods A retrospective review of five patients who underwent expanded endoscopic endonasal surgery for various pathologies (two craniopharyngiomas, two tuberculum meningiomas, and one planum meningioma) was performed. Skull base closure was performed using a one-piece modified gasket seal technique. Primary outcome measures included postoperative cerebrospinal fluid (CSF) leaks and donor site morbidity.Results There were no postoperative CSF leaks. Two patients experienced aseptic meningitis treated with a 14-day course of steroids. Two patients experienced new postoperative chronic/recurrent sinusitis treated with oral antibiotics and topical nasal therapy. There was no donor site morbidity such as infection, hematoma, or hernias.Conclusions The one-piece modified gasket-seal closure is a safe and effective method for reconstruction of endonasal defects of the anterior skull base. Rectus sheath fascia is an appropriate dural substitute for free tissue grafting with low donor site morbidity. The construction of the one-piece graft significantly decreases operative time and lowers the learning curve for multilayered closure.
Keywords: CSF leak; endoscopic; skull base; gasket seal